Technology-integrated dementia care: trial results. (2nd September 2019) - Rostill, Helen; Nilforooshan, Ramin; Barnaghi, Payam; Morgan, Amanda
Abstract : With dementia on the rise and care staff already overstretched, solutions need to be found to ensure the health and wellbeing of people living with the condition. Helen Rostill, Ramin Nilforooshan and Payam Barnaghi ran a trial with an IoT-led monitoring system.